Revitalisasi Penjualan: Strategi Pemasaran Digital untuk Meraih Sukses Bisnis Roti dan Kue bersama Holand Bakery - Lontar, Benediktus; Qadri, Andi; Melati, Vegi; Ryan, Muhammad Akhsan; Dinsar, Arfandi (Jurnal Ilmiah Multidisiplin Amsir, 2022)
The aim of this research is to optimize digital marketing strategies to increase the sales of bread and cakes. Important factors to consider include product quality, brand image, and pricing strategy. Online marketing methods are utilized, including promotions through social media and SEO. Data analysis is conducted to understand consumer preferences and implement effective strategies. Implementing online marketing strategies that focus on product quality and brand image can increase sales and maintain consumer satisfaction.